Current issues in wind energy meteorology. (5th August 2014) - Emeis, Stefan
ABSTRACT This review discusses some of the current issues in wind energy meteorology from the viewpoint of a meteorologist. The focus is on four major subjects: (1) the wind potential, (2) the influence of major terrain inhomogeneities on this wind potential, (3) diurnal wind variations and (4) the impact of wind turbines and wind parks on the flow. The wind potential is addressed by describing vertical profiles of wind and turbulence, trying to give profile laws that are valid throughout the major part of the atmospheric boundary layer and specifying specific offshore turbulence conditions. Flow over forests and gently sloping hills are presented as two examples for the very broad spectrum of possible terrain inhomogeneities. Diurnal variations of wind speed turn out to be height dependent. A major diurnal variation, the formation of low‐level jets, is discussed in detail. Finally, wakes of single turbines and of entire wind parks are addressed and an analytical model for park efficiency and wake is presented. This review gives only a short overview on the spectrum of issues in wind energy meteorology. A few analytical approaches are presented to explain first‐order effects. Detailed investigations of wind and turbulence conditions usually require the use of non‐linear high‐resolution flow models.